The Influence of Marketing Information Systems on Customer Loyalty in the Denpasar Automotive Industry in the Time of Covid-19 - Kelvin Hendrata; Putu Ngurah Suyatna Yasa; Ni Luh Putu Indiani (Universitas Warmadewa, 2021)
Corona Virus Disease (Covid-19) in a pandemic situation, various elements are affected, one of which is the automotive sector. Companies are required to increase profits where in the current conditions loyal customers are the basis of their market. arketing information systems are important to increase customer loyalty during a pandemic accompanied by quality service and customer satisfaction. This study aims to determine the correlation between the marketing information system mediated by service quality, customer satisfaction, and customer loyalty in the automotive industry in Denpasar. The sample method uses random sampling with accidental sampling through distributing questionnaires that are measured using a Likert scale. The research sample consisted of 80 respondents, namely customers who had been to an authorized car dealer in the city of Denpasar. The results showed that the marketing information system had a positive and insignificant effect on customer loyalty. Marketing information systems have a significant positive effect on service quality and customer satisfaction. Service quality has a significant positive effect on customer loyalty, besides that customer satisfaction has a positive and insignificant effect on loyalty. Service quality and customer satisfaction are perfect mediations of the relationship between marketing information systems and customer loyalty, so this shows that marketing information systems are needed to maintain customer loyalty which is assisted by service quality and customer satisfaction so that companies can survive the Covid-19 era, especially in the industry automotive.